Objective assessment of skin tightening in Asians using a water-filtered near-infrared (1,000–1,800 nm) device with contact-cooling and freezer-stored gel - Tanaka Y; Tsunemi Y; Kawashima M; Tatewaki N; Nishida H (Dove Medical Press, 2013)
Yohei Tanaka,1–3 Yuichiro Tsunemi,2 Makoto Kawashima,2 Naoto Tatewaki,3 Hiroshi Nishida31Clinica Tanaka Plastic, Reconstructive Surgery and Anti-aging Center, Nagano, 2Department of Dermatology, Tokyo Women's Medical University, Tokyo, 3Department of Applied Life Sciences, Niigata University of Pharmacy and Applied Life Sciences, Niigata, JapanBackground: Near-infrared has been shown to penetrate deeper than optical light sources independent of skin color, allowing safer treatment for the Asian skin type. Many studies have indicated the efficacy of various types of devices, but have not included a sufficiently objective evaluation. In this study, we used three-dimensional imaging for objective evaluation of facial skin tightening using a water-filtered near-infrared device.Methods: Twenty Japanese patients were treated with the water-filtered near-infrared (1,000–1,800 nm) device using a contact-cooling and nonfreezing gel stored in a freezer. Three-dimensional imaging was performed, and quantitative volume measurements were taken to evaluate the change in post-treatment volume. The patients then provided their subjective assessments.Results: Objective assessments of the treated cheek volume evaluated by a three-dimensional color schematic representation with quantitative volume measurements showed significant improvement 3 months after treatment. The mean volume reduction at the last post-treatment visit was 2.554 ± 0.999 mL. The post-treatment volume was significantly reduced compared with the pretreatment volume in all patients (P < 0.0001). Eighty-five percent of patients reported satisfaction with the improvement of skin laxity, and 80% of patients reported satisfaction with improvement of rhytids, such as the nasolabial folds. Side effects, such as epidermal burns and scar formation, were not observed throughout the study.Conclusion: The advantages of this water-filtered near-infrared treatment are its high efficacy for skin tightening, associated with a minimal level of discomfort and minimal side effects. Together, these characteristics facilitate our ability to administer repeated treatments and provide alternative or adjunctive treatment for patients, with improved results. This study provides a qualitative and quantitative volumetric assessment, establishing the ability of this technology to reduce volume through noninvasive skin tightening.Keywords: objective evaluation, quantitative volume measurement, skin laxity, three-dimensional imaging, rhytids